On an Antenna Design for 2D Scalar Near-Field Microwave Tomography - Bayat, Nozhan; Mojabi, Puyan (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Some desired antenna specifications for performing two-dimensional (2D) transverse magnetic (TM) microwave tomography imaging are presented and discussed. These desired specifications are governed by the need to reduce the discrepancy between the 3D measurement configuration and the utilized 2D TM inversion algorithm, as well as the desire to enhance the achievable image accuracy and resolution. Driven by these specifications, an existing compact ultrawideband antenna element is modified. These modifications attempt to make the near-field distribution of this antenna more focused in the two orthogonal planes in the forward near-field zone of the antenna, while keeping its physical size relatively small and maintaining multiple frequencies of operation for this antenna. The final antenna has a physical size of 26×29×38.5 mm3 and can operate at two different frequency bands (2.34-5.04 GHz and 8.06-13 GHz based on the |S11| ?-8 dB impedance bandwidth definition). The measured near-field distribution of this antenna is presented in the imaging plane and the plane perpendicular to the imaging plane.